2023
DOI: 10.3390/ani13142247
|View full text |Cite
|
Sign up to set email alerts
|

Handling and Training of Wild Animals: Evidence and Ethics-Based Approaches and Best Practices in the Modern Zoo

Abstract: There is an ethical responsibility to provide all animals living in human care with optimal and positive well-being. As animals living in zoos and aquariums frequently interact with their human caregivers as part of their daily care routines, it is both relevant and essential to consider the impact of these interactions on animal well-being. Allowing animals to have choice and control in multiple areas of their lives, such as by providing opportunities for them to voluntarily participate in their own care thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 187 publications
0
13
0
Order By: Relevance
“…Aversive management methods—negative reinforcement and positive punishment—can mislead a handler into believing their coercive strategies are successful because effective punishment can reinforce the punisher [ 20 ]. Research shows capture and handling can be stressful for most ambassador animals, including reptiles [ 18 ]. Studies have shown that aversive training methods negatively affect animal welfare and that there is no evidence that aversive training methods are more effective than reward-based training [ 14 ].…”
Section: Moving Toward a More Positive Futurementioning
confidence: 99%
See 4 more Smart Citations
“…Aversive management methods—negative reinforcement and positive punishment—can mislead a handler into believing their coercive strategies are successful because effective punishment can reinforce the punisher [ 20 ]. Research shows capture and handling can be stressful for most ambassador animals, including reptiles [ 18 ]. Studies have shown that aversive training methods negatively affect animal welfare and that there is no evidence that aversive training methods are more effective than reward-based training [ 14 ].…”
Section: Moving Toward a More Positive Futurementioning
confidence: 99%
“…Knowing the science provides a good foundation, with the recognition that some individuals will be more adept at understanding and applying the training concepts than others. The goal should be for all personnel working with ambassador animals to participate in ongoing education to refine their knowledge and training skills so as to achieve greater consistency [ 18 ]. The ultimate goal should be to create an institutional memory in training competency, where every person working with ambassador animals can apply their skills equally to every animal in the collection.…”
Section: A Model For Improved Ambassador Animal Welfarementioning
confidence: 99%
See 3 more Smart Citations